Independent APOE4 knock‐in mouse models display reduced brain APOE protein, altered neuroinflammation, and simplification of dendritic spines. Issue 3 (29th July 2022) - Sepulveda, Jordy; Luo, Nancy; Nelson, Matthew; Ng, Christi Anne S.; Rebeck, George William
Abstract: APOE is an immunomodulator in the brain and the major genetic risk factor for late‐onset Alzheimer's disease (AD). Targeted replacement APOE mice ( APOE ‐TR) have been a useful tool to study the effects of APOE isoforms on brain neurochemistry and activity prior to and during AD. We use newly available APOE knock‐in mice (JAX‐APOE) to compare phenotypes associated with APOE4 across models. Similar to APOE4‐TR mice, JAX‐E4 mouse brains showed 27% lower levels of APOE protein compared with JAX‐E3 ( p < 0.001). We analyzed several neuroinflammatory molecules that have been associated with APOE genotype. SerpinA3 was much higher in APOE4 ‐TR mice to APOE3 ‐TR mice, but this effect was not seen in JAX‐APOE mice. There were higher levels of IL‐3 in JAX‐E4 brains compared with JAX‐E3, but other neuroinflammatory markers (IL6, TNFα) were not affected by APOE genotype. In terms of neuronal structure, basal dendritic spine density in the entorhinal cortex was 39% lower in JAX‐E4 mice compared with JAX‐E3 mice ( p < 0.001), again similar to APOE‐TR mice. One‐week treatment with ibuprofen significantly increased dendritic spine density in the JAX‐E4 mice, consistent with our previous finding in APOE ‐TR mice. Behaviorally, there was no effect of APOE genotype on Barnes Maze learning and memory in 6‐month‐old JAX‐APOE mice. Overall, the experiments performed in JAX‐APOE mice validated findings from APOE ‐TR mice, identifying particularly strong effects of APOE4 genotype on lower APOE protein levels and simplified neuron structure. These data demonstrate pathways that could promote susceptibility of APOE4 brains to AD pathological changes. Abstract : We compared phenotypes associated with APOE4 in two targeted replacement APOE mice models, APOE ‐TR and JAX‐APOE mice. APOE4 genotype results in reduced APOE protein levels, altered inflammatory markers at baseline, and simplified dendritic spine density compared with APOE3 across the models. One‐week ibuprofen treatment restored dendritic spine in APOE4 mice. We conclude that the strongest effects of the APOE4 genotype are decreased APOE protein levels and simplified neuron structure, pathways that promote brain susceptibility to AD.